1988
DOI: 10.1111/j.1471-4159.1988.tb02936.x
|View full text |Cite
|
Sign up to set email alerts
|

Solubilization and Characterization of Calcitonin Gene‐Related Peptide Binding Site from Porcine Spinal Cord

Abstract: The binding site for calcitonin gene-related peptide (CGRP) was solubilized with 3-[(3-cholamidopropyl)dimethylammonio]-1-propane sulfonate (CHAPS) in an active form from porcine spinal cord. 125I-labeled human alpha-CGRP (125I-CGRP) binding to the solubilized protein was determined by filtration using a GF/B glass filter. The maximal binding activity (approximately 60% of the crude membrane fraction) was obtained with 5 mM CHAPS. 125I-CGRP binding to the solubilized protein was of high affinity, saturability,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Specific CGRP receptors have been found in porcine coronary arteries (M r 90,000 and 70,000) and in the atria (318). In the porcine spinal cord, only the 70,000 M r form was identified (318)(319)(320)(321). The reported M r of the CGRP-binding protein measured by autoradiography after cross-linking with bifunctional reagents varies from 13,700 to 400,000 (296, 292-301, 315-322).…”
Section: Isolation Cloning Sequencing and Characterizing Of Recmentioning
confidence: 99%
“…Specific CGRP receptors have been found in porcine coronary arteries (M r 90,000 and 70,000) and in the atria (318). In the porcine spinal cord, only the 70,000 M r form was identified (318)(319)(320)(321). The reported M r of the CGRP-binding protein measured by autoradiography after cross-linking with bifunctional reagents varies from 13,700 to 400,000 (296, 292-301, 315-322).…”
Section: Isolation Cloning Sequencing and Characterizing Of Recmentioning
confidence: 99%
“…We previously found that CHAPS solubilized the binding sites retaining the specific binding activity to CGRP from the spinal cord but not from coronary arteries, atria, or ventricles (Hiroshima et al, 1988). In the present study, among the various types of detergents so far examined, only the nonionic detergent I922 Y. SANO ET AL.…”
Section: Discussionmentioning
confidence: 51%
“…The binding assay of the crude membrane as well a:< the solubilized fraction was carried out according to the method described previously (Hiroshima et al, 1988). In brief, the crude membrane or solubilized fractions (100 p l ) were mixed with 900 pl of I2'1-human a-CGRP (18-23 pM) in buffer A containing 1% digitonin in the presence or absence of 1.0 pLM unlabeled human a-CGRP.…”
Section: Solubilization and Radioligand Assay Of Cgrp-binding Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of a specific receptor (Foord & Graig, 1987;Hiroshima et al 1988) and the ability of CGRP to activate adenylate cyclase suggest that the stimulatory effect of CGRP on ICa may be mediated by a GTP-binding protein (Neer & Clapham, 1988;Birnbaumer et al 1989). We have obtained evidence for involvement of GTP-binding protein (s) in these CGRP effects.…”
Section: Cgrp-induced Activation Of Ik and The Action Potential Changementioning
confidence: 65%